Analisis faktor-faktor yang memengaruhi kualitas laporan keuangan pada kementerian pekerjaan umum dan perumahan rakyat dengan pemanfaatan teknologi informasi sebagai pemoderasi - Karina, Rieni; Nirwana, Nirwana; Indrijawati, Aini (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The central government is obliged to provide quality financial reports as a means of accountability. A total of 178 respondents participated in the research conducted at the Ministry of PUPR with a sample of 89 work units using the purposive sampling technique. Questionnaires are used to collect primary data using a survey methodology. The analytical methods used are multiple regression analysis and moderate regression analysis. The research findings show that the application of government accounting standards, human resource competencies, internal control systems, organizational commitment, and the leadership style of the Ministry of PUPR has a positive and significant effect on the quality of financial reports. This can be seen from the level of significance of each variable in the t-test of multiple linear regression analysis without moderation, which is less than 5%. Second, the use of information technology, which includes tools, financial data management, and maintenance, can positively influence the relationship between organizational commitment to the quality of the Ministry of PUPR's financial reports and SAP implementation factors. However, the quality of financial reports can be negatively affected by the interaction of HR competencies with the use of information technology. Based on the t-test of moderate regression analysis (MRA), the use of information technology is not able to moderate the effect of SPI interactions and leadership style interactions on the quality of financial reports at the Ministry of PUPR.